2021
DOI: 10.5114/jcb.2021.105846
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate brachytherapy as monotherapy for low- and intermediate-risk prostate cancer: long-term experience of Swedish single-center

Abstract: Purpose: Until now, most long-term results for brachytherapy only has been published for low-dose-rate (LDR) seeds. Due to radiobiology reasons, high-dose-rate (HDR) mono-brachytherapy is of growing interest. The aim of the study was to report long-term biochemical control rate and toxicities with HDR monotherapy.Material and methods: This was a retrospective single-institution experience, including 229 men, clinically staged T1c-T2b, Gleason 3 + 3 (prostate specific antigen (PSA) ≤ 15), or Gleason 3 + 4 (PSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…( 25 ), whereas iPSA with a cut off of 10 ng/ml and age were of statistical significance in the study by Johansson et al. ( 26 ), both treating low-, intermediate-risk PCA-patients with HDR-BRT as monotherapy. In the univariate analysis of 1100 low- and intermediate-risk PCA-patients treated with LDR-BRT, Crook et al.…”
Section: Discussionmentioning
confidence: 90%
“…( 25 ), whereas iPSA with a cut off of 10 ng/ml and age were of statistical significance in the study by Johansson et al. ( 26 ), both treating low-, intermediate-risk PCA-patients with HDR-BRT as monotherapy. In the univariate analysis of 1100 low- and intermediate-risk PCA-patients treated with LDR-BRT, Crook et al.…”
Section: Discussionmentioning
confidence: 90%
“…A retrospective study on a long term treatment outcome is recently reported by a Swedish single-center study [ 25 ]. The treatment was a high-dose rate brachytherapy applied as monotherapy for treating low- and intermediate-risk prostate cancer patients.…”
Section: Methodsmentioning
confidence: 99%
“… Individual TCP distributions obtained for the parameter values shown in Equations (6) and (7). ( a )—individual TCP distribution for the three-fraction regimen (5 failures out of 107 patients (4.7%) [ 25 ]); ( b )—individual TCP distribution for the two-fraction regimen (15 failures out of 103 patients (14.6%) as reported in [ 25 ]). …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations